PENGARUH SELF CONTROL, GAYA HIDUP CASHLESS DAN BUY NOW PAY LATER TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA - Siti Nurul Fathimah; Evi Veronika Dewi; Muhammad Ikhsan Febriyanto; Erliana Erliana (Universitas Dharmawangsa, 2026)
Financial management behavior is an important aspect for students in maintaining financial stability amid the rapid development of digital financial technology. This study aims to analyze the effect of self control, cashless lifestyle, and Buy Now Pay Later on the financial management behavior of students at Universitas Pamulang. The study used a quantitative associative approach with purposive sampling involving 100 student respondents. Data were collected through Likert-scale questionnaires and analyzed using SPSS 27 through validity, reliability, classical assumption, simple regression, multiple regression, correlation, determination, t-test, and F-test procedures. The findings indicate that self control has a positive and significant effect on students’ financial management behavior. Cashless lifestyle also contributes positively to financial management behavior, while Buy Now Pay Later influences students’ financial decision-making and consumption behavior. Simultaneously, self control, cashless lifestyle, and Buy Now Pay Later explain 79.6% of the variation in students’ financial management behavior, indicating a strong combined effect. The results imply that improving self control and encouraging wise use of digital payment systems and Buy Now Pay Later services can strengthen students’ financial management behavior and support financial literacy in the digital era.